PRINSIP ADAT ACEH TENTANG PERWALIAN ANAK KORBAN GEMPA DAN TSUNAMI DI BANDA ACEH DAN ACEH BESAR - LailaM Rasyid; Romi Asmara (Jurnal Dinamika Hukum, 2012)
Earthquake and tsunami that occurred on December 26, 2004 has brought heavy casualties and one of them are children who lost parents. One of the efforts undertaken to protect them is by appointment or a trust either by others or close relatives. In this study known a few years after the Tsunami occurred, determining application rates of adoption / guardianship quite a lot of happenned in Banda Aceh and Aceh Besar, and motivation to perform the average because of economic interests related to money wages, pension or insurance held by children. The process of removal/custody of children is predominantly used by indigenous peoples in the community, and formal legal principle was used when dealing with law. In the field can be found that property management should a supervision from geuchik,tuha peut and Imum Meunasah, Tuha peut which is the Baitul Mal Village officials to prevent misuse. Keywords: Child, Victim, earthquake, Aceh